PESCADORAS EN LA CALETA DE CHORRILLOS-LIMA - Cazorla Zen, Carmen (2017)
It describes and analyzes some elements of artisanal fisheries and participation of women as protagonists. Also, understand that fisherwomen think of their work, if there is any taboo around their participation and how they respond against the restrictions that are developing around this economic activity.